Neotectonic effects of glacial erosion and deglaciation on the Sangre de Cristo Mountains, southern Colorado - Hurtado, Cecilia, author; Gallen, Sean, advisor; Singleton, John, committee member; McGrath, Daniel, committee member; Denning, Scott, committee member (Colorado State University. Libraries, 2023)
Interrelations between climate and tectonics are important to the development of active mountain belts, but rarely are there natural examples that lend themselves to studying the effects of climate on tectonics. The Sangre de Cristo Mountains in southern Colorado provide an optimal natural laboratory to explore the effects of alpine valley glaciation on surface uplift of the footwall and on the active extensional normal fault system in the northern Rio Grande rift. This region has experienced changes in surface loads associated with long-term glacial erosion and sedimentation over the course of the Quaternary, as well as shorter-term deglaciation after the Last Glacial Maximum. These changing loads correspond with stress changes that affect the flexural isostatic response of the lithosphere, and further act as clamping or unclamping stresses on the Sangre de Cristo fault that bounds the western margin of the mountain range. This work quantifies the masses and spatial distributions of these various loads and models the associated flexural isostatic response to estimate potential uplift and subsidence patterns in the study area that could be attributed to climate-driven mechanisms. The glacially-scoured footwall material was estimated by using remnants of the fluvial reaches downstream of glaciated drainage basins, reconstructing the paleofluvial topography, and subtracting it from the modern topography. The quantification of the deposited sediment in the San Luis Basin was measured from an interpolated surface tethered by existing drill cores, geophysical data, and geologic maps. Lastly, the glacial extents and thicknesses were constructed using a simple numerical modeling tool, GlaRe, constrained by preserved depositional and erosional evidence of glaciers. Isostatic responses were calculated using a flexure model with two effective elastic thickness (Te) values, 2 km and 5 km, and stress changes on faults at depth were calculated using an analytical line load model. The results estimate ~29 m of footwall uplift and ~47 m of subsidence in the hanging wall for a realistic Te of 5 km, and footwall uplift of ~48 m and a hanging wall subsidence of ~80 m for an independently calibrated Te of 2 km. Importantly, while topographic reconstructions indicate an ~50 m reduction in mean footwall elevations, isostatic rebound pushes mountain peaks upward by tens of meters. Footwall uplift due to deglaciation has a response of 4 m and 6 m, for a Te of 5 km and a Te of 2 km, respectively. The Sangre de Cristo fault trace was mapped to quantify the offset of fault scarps on Quaternary alluvial fans to determine the spatial and temporal patterns of offset along-strike of the fault. Fault offset magnitudes correlate with glacial domains, and fault slip rates correlate with the post-glacial spatial pattern of isostatic uplift, indicating an unambiguous link between deglaciation and elevated fault activity. This work demonstrates that (1) differential glacial erosion reduces mean footwall elevations, but the associated isostatic response drives surface uplift of mountain peaks, and (2) seismicity along normal faults could be amplified by load changes associated with climate-driven mechanisms, which will become increasingly important as we continue in a period of anthropogenic warming and deglaciation.
Keywords: isostasy; stress; fault; surface uplift; Sangre de Cristo